Book review: Reconstructing Marriage: The legal status of relationships in a changing society. By Caroline Sörgjerd. Cambridge; Antwerp; Portland: Intersentia Publishing, Ltd., 2012. Pp. vii, 358. ISBN: 978-1-78068-037-8 - Yatsunska, Olena (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
-